Effects of Footbaths with Mustard, Ginger, or Warm Water Only on Objective and Subjective Warmth Distribution in Healthy Subjects: A Randomized Controlled Trial. (December 2018) - Vagedes, J.; Helmert, E.; Kuderer, S.; Müller, V.; Voege, P.; Szőke, H.; Valentini, J.; Joos, S.; Kohl, M.; Andrasik, F.
Highlights: First RCT analyzing the efficacy of footbaths with warm water only and warm water combined either with sinapis nigra (mustard) or zingiber officinale (ginger) Significant increases in skin temperature (thermography) occurred at the feet after all conditions Mustard and ginger increased warmth perception at the feet more than warm water alone, with only the effects for ginger enduring at the brief follow-up. Abstract: Objective: To analyze the short-term thermogenic effects of footbaths with warm water alone (WA) versus when combined with medicinal powders. Design: Randomized controlled trial with cross-over. Interventions and Outcomes: Seventeen healthy volunteers (mean age 22.1 years, SD = 2.4; 11 female) received three footbaths with WA or WA combined with mustard (MU) or ginger (GI) in a randomized order. Self-perceived warmth (Herdecke warmth perception questionnaire) and actual skin temperatures (thermography) were assessed before (t0), immediately after footbaths (t1), and 10 minutes later (t2). The primary outcome was perceived warmth in the feet. Secondary outcomes were warmth perception in the face, hands and overall, as well as actual skin temperature in the feet, face, and hands. Results: Perceived warmth at the feet (primary outcome) increased significantly (all p 's < .001) for MU and GI at t1 as well as for GI at t2 when compared to t0 with high effect sizes. At t2, GI differed significantly from WA ( p < .001) and MU ( p = .048). With regards to the secondary measures of outcome, no significant effects were seen for perceived warmth at the face or hands. Overall warmth was significantly higher at t1 compared to t0 ( p = .01). Thermography assessments of skin temperature at the feet at t1 increased after all conditions ( p < .001). No effects were seen in the face. At the hands, temperature decreased at t1 ( p = .02) and t2 compared to t0 ( p < .001). Conclusion: The present study provides preliminary evidence that mustard and ginger increase warmth perception at the feet more than warm water alone, with only the effects for GI enduring at the brief follow-up.